Recent advances in the application of microbiota transplantation in chickens - Haoran Zhao; Luke Comer; Muhammad Zeeshan Akram; Matthias Corion; Yang Li; Nadia Everaert (Journal of Animal Science and Biotechnology)
Abstract Extensive evidence demonstrates that a healthy and well-balanced gut microbiota profoundly influences host nutrient absorption, immunity, and metabolism. Unlike mammals, early microbiota colonization in commercial poultry largely depends on the environment as chicks hatch in incubators under a relatively sterile environment (egg and incubator sterilization) without maternal-offspring interaction. The early gut microbiota remains unsaturated, providing a critical window for modulation and influencing the subsequent microbiota succession, which may have long-term health outcomes. Microbiota transplantation (MT) involves transferring the microbiota from a donor to a recipient to modulate the recipient’s microbiota toward a desired state. Successfully applied in human medicine, MT is also gaining attention in poultry production to modulate intestinal health. This review comprehensively explores factors affecting MT, its mechanisms, and its potential applications in chickens, providing insights for further research and commercial use.